2009
DOI: 10.1088/0004-637x/701/2/865
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Synthesis Modeling of the X-Ray Spectrum of Gro J1655-40 Taken During the 2005 Outburst

Abstract: The spectrum from the black hole X-ray transient GRO J1655-40. obtained using the Chandra High Energy Transmission Grating (HETG) in 2005 is notable as a laboratory for the study of warm absorbers, and for the presence of many lines from odd-Z elements between Na and Co (and Ti and Cr) not previously observed in X-rays. We present synthetic spectral models which can be used to constrain these element abundances and other parameters describing the outflow from the warm absorber in this object. We present result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
190
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(207 citation statements)
references
References 38 publications
16
190
1
Order By: Relevance
“…These blueshifts seem too large, compared to the shifts of ∼400 km s −1 obtained by Ueda et al (2004) for GX 13+1 and of ∼300-1600 km s −1 in microquasars (e.g. Kallman et al 2009;Ueda et al 2009;see however Miller et al 2011 for a recently reported blueshift of 3100 ± 400 km s −1 in a Chandra A50, page 12 of 17 HETGS observation of IGR J17480-2446). Unfortunately, we did not detect any discrete absorption features from the warm absorber in the RGS, which has a much better energy resolution than EPIC.…”
Section: Photoionised Absorptionmentioning
confidence: 83%
“…These blueshifts seem too large, compared to the shifts of ∼400 km s −1 obtained by Ueda et al (2004) for GX 13+1 and of ∼300-1600 km s −1 in microquasars (e.g. Kallman et al 2009;Ueda et al 2009;see however Miller et al 2011 for a recently reported blueshift of 3100 ± 400 km s −1 in a Chandra A50, page 12 of 17 HETGS observation of IGR J17480-2446). Unfortunately, we did not detect any discrete absorption features from the warm absorber in the RGS, which has a much better energy resolution than EPIC.…”
Section: Photoionised Absorptionmentioning
confidence: 83%
“…From a detailed analysis of the absorption line profile, they detected multiple components in the wind, where a more ionized part was located at a smaller radius. After Miller et al (2006) first reported the Chandra/HETG result, the unusual wind in GRO J1655−40 has been revisited many times from both observational and theoretical points of view (Netzer 2006;Miller et al 2008;Kallman et al 2009;Luketic et al 2010;Neilsen & Homan 2012;Higginbottom & Proga 2015). Many previous studies were based on the assumption that the wind was optically thin and launched at a few percent of the Eddington luminosity, in constructing photoionized plasma models and performing hydrodynamic simulations.…”
Section: Where Is the Hidden Compton-thick Wind Located?mentioning
confidence: 99%
“…While the iron K emission line exists in almost all X-ray sources , K-line features from silicon have also been commonly observed (Kaspi et al 2001(Kaspi et al , 2002Kallman et al 2009). Young et al (2005) reported the detection of H-like Si absorption lines in MCG 6-30-15 and determined the outflow velocity by measuring the line blueshift.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the information (such as the column density, electron temperature, ionization states, wind velocity, and abundances) obtained by analysis of these high-resolution spectra, mechanisms that drive and heat plasmas can be deduced. Determining the abundance of various elements can shed light on the chemical evolution and origin of the hosting galaxy (Kallman et al 2009). The L-shell transition lines from low-ionization ions of Si are used to identify them in UV spectra (Ebrero et al 2013).…”
Section: Introductionmentioning
confidence: 99%